2014
DOI: 10.1515/shll-2014-1169
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Variation And Change In Spanish Peripheral Fricatives

Abstract: The variation between labial and velar fricatives (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Earlier research determined how linguistic categories, such as the place of articulation and voicing shape the spectral properties of fricatives (e.g., Hughes and Halle, 1956 ; Nittrouer et al, 1989 ; Baum and McNutt, 1990 ; Ladefoged and Maddieson, 1996 ; Jongman et al, 2000 ; Fox and Nissen, 2005 ; Shadle, 2010 ; Iskarous et al, 2011 ; Koenig et al, 2013 ), yet most of these findings are based on acoustic evidence from a single language variety (e.g., for Korean fricatives see Cho et al, 2002 , for English fricatives see Tabain, 1998 ; Jongman et al, 2000 ; Iskarous et al, 2011 ). Despite the fact that a number of earlier studies showed that social factors, such as gender and age (e.g., see Jongman et al, 2000 ; Fox and Nissen, 2005 ; Li et al, 2016 ), education, social identity, social networks (e.g., Baran, 2014 ) and the place of origin, urban vs. rural (Dubois and Horvath, 1998 ; Kochetov, 2006 ; Stuart-Smith, 2007 ; Mazzaro, 2011 ) have significant effects on fricatives, the effects of dialect on fricatives acoustic structure are understudied.…”
Section: Introductionmentioning
confidence: 97%
“…Earlier research determined how linguistic categories, such as the place of articulation and voicing shape the spectral properties of fricatives (e.g., Hughes and Halle, 1956 ; Nittrouer et al, 1989 ; Baum and McNutt, 1990 ; Ladefoged and Maddieson, 1996 ; Jongman et al, 2000 ; Fox and Nissen, 2005 ; Shadle, 2010 ; Iskarous et al, 2011 ; Koenig et al, 2013 ), yet most of these findings are based on acoustic evidence from a single language variety (e.g., for Korean fricatives see Cho et al, 2002 , for English fricatives see Tabain, 1998 ; Jongman et al, 2000 ; Iskarous et al, 2011 ). Despite the fact that a number of earlier studies showed that social factors, such as gender and age (e.g., see Jongman et al, 2000 ; Fox and Nissen, 2005 ; Li et al, 2016 ), education, social identity, social networks (e.g., Baran, 2014 ) and the place of origin, urban vs. rural (Dubois and Horvath, 1998 ; Kochetov, 2006 ; Stuart-Smith, 2007 ; Mazzaro, 2011 ) have significant effects on fricatives, the effects of dialect on fricatives acoustic structure are understudied.…”
Section: Introductionmentioning
confidence: 97%